Biodegradation of metformin and guanylurea by aerobic cultures enriched from sludge - Briones, Rowena M.; Zhuang, Wei-Qin; Sarmah, Ajit K. (Environmental pollution (1987), 2018)
Sewage sludge from a municipal wastewater treatment facility employing activated sludge process was pre-incubated with varying substrates and mixtures of substrates including metformin (MET), guanylurea (GUA) and glucose. The biomass from enriched cultures separately utilising MET and glucose/GUA was then used to investigate the kinetics of aerobic biodegradation of MET and GUA, respectively, as individual substrates in batch reactors. The results showed that GUA can be completely degraded as a nitrogen source when glucose is provided as a carbon and energy source. On the contrary, MET can be biodegraded as a sole carbon and energy source. However, formation of by-product GUA in solution, which acts as a nitrogen source, rapidly increased the degradation rate of MET resembling autocatalytic behaviour. At low starting concentration of 5 mg/L, the specific substrate utilisation rates of MET and GUA were 0.0033 day−1 and 0.0013 day−1, respectively, which is reported first time in this study. Out of the five biodegradation kinetic models used to describe substrate utilisation, the Quiroga-Sales-Romero (QSR) model was found to predict the measured MET and GUA degradation profile well supported by the goodness of fit parameters. Furthermore, the QSR model was able to describe the autocatalytic degradation of MET and the incomplete biodegradation of GUA in solution. [Display omitted] •Activated sludge culture was enriched with metformin (MET) and/or guanylurea (GUA)•Glucose was also added to some cultures as co-substrate and carbon/energy source•Rapid and complete degradation of MET was observed with concomitant formation of GUA•Absence of glucose led to incomplete degradation of GUA in solution•Glucose provides carbon source for microbes to achieve complete GUA degradation The aerobic biodegradation of metformin and guanylurea as individual substrates was studied in batch reactors using sewage sludge that were pre-incubated with these target compounds.